Undergraduate Research Experience Models: A systematic review of the literature from 2011 to 2021 - Zubair, Ahmad (2022)
Undergraduate research experiences (UREs) impart a great deal of knowledge to undergraduate students, enhance the research capital of institutes, and authenticate the country's educational outcomes. To effectively assimilate these benefits, the URE designers have proposed many different learning models. However, there is little work done to assess and compare the effectiveness of these varying learning models being adopted in various disciplines. Hence, this article provides an educational research review on the effective pedagogical models in URE to enhance the research experiences of undergraduate students. We initially screened 331 articles and finally compared 67 studies between 2011 and 2021 ranging in different disciplines to understand and weigh out the influence of these URE models with a special focus on the ones in STEM (science, technology, engineering, and mathematics) related fields. This study also indicates the factors that mediate a constructive relationship between students and specific URE models like the Course-based Undergraduate Research Experience (CURE) model in juxtaposing with other traditional and hybrid URE models. Most models have been implemented to biology-related fields and experienced in the United States (U.S.). This depicts a gap in research for the effective implementation of URE in other STEM fields and other countries. Moreover, the CURE model was found to be an effective practice providing large-scale research opportunities to students. However, it is majorly focused on the life sciences field and needs more extensive research in the other disciplines. Also, being comparatively a newer form of URE, there is room for more research in developing this model. While other traditional and hybrid models demonstrated positive characteristics, large reforms are needed for their efficient implementation. Finally, we summarize the strengths and limitations of the URE models from the last decade to highlight the practically successful models for future designers to be implemented in different disciplines.